The Vasopressin Receptor 2 Mutant R137L Linked to the Nephrogenic Syndrome of Inappropriate Antidiuresis (NSIAD) Signals through an Alternative Pathway that Increases AQP2 Membrane Targeting Independently of S256 Phosphorylation - Marianna Ranieri (Cells, 2020)
NSIAD is a rare X-linked condition, caused by activating mutations in the AVPR2 gene coding for the vasopressin V2 receptor (V2R) associated with hyponatremia, despite undetectable plasma vasopressin levels. We have recently provided in vitro evidence that, compared to V2R-wt, expression of activating V2R mutations R137L, R137C and F229V cause a constitutive redistribution of the AQP2 water channel to the plasma membrane, higher basal water permeability and significantly higher basal levels of p256-AQP2 in the F229V mutant but not in R137L or R137C. In this study, V2R mutations were expressed in collecting duct principal cells and the associated signalling was dissected. V2R-R137L and R137C mutants had significantly higher basal pT269-AQP2 levels -independently of S256 and PKA-which were reduced to control by treatment with Rho kinase (ROCK) inhibitor. Interestingly, ROCK activity was found significantly higher in V2R-R137L along with activation of the Gα12/13–Rho–ROCK pathway. Of note, inhibition of ROCK reduced the basal elevated osmotic water permeability to control. To conclude, our data demonstrate for the first time that the gain-of-function mutation of the V2R, R137L causing NSIAD, signals through an alternative PKA-independent pathway that increases AQP2 membrane targeting through ROCK-induced phosphorylation at S/T269 independently of S256 of AQP2.